Impact of Timing and Dosage of a Fluoroquinolone Treatment on the Microbiological, Pathological, and Clinical Outcomes of Calves Challenged with Mannheimia haemolytica - Lhermie, Guillaume; Ferran, Aude A.; Assié, Sébastien; Cassard, Hervé; El Garch, Farid; Schneider, Marc; Woerhlé, Frédérique; Pacalin, Diane; Delverdier, Maxence; Bousquet-Mélou, Alain; Meyer, Gilles (Frontiers in Microbiology, 2016)
The efficacy of an early and low inoculum-adjusted marbofloxacin treatment was evaluated on microbiological and clinical outcomes in calves infected with 4.107 CFU of Mannheimia haemolytica A1. Twenty-two calves were included based on their rectal temperature rise in the 10 h after challenge and allocated in 4 groups, receiving a single intramuscular injection of saline (CON), 2 mg/kg marbofloxacin 2-4 h after inclusion (early treatment, E2), 2 or 10 mg/kg marbofloxacin 35-39 h after inclusion (late treatments, L2, L10). In CON calves, M. haemolytica DNA loads in bronchoalveolar lavages continuously increased from inclusion to day 4, and were associated with persistent respiratory clinical signs and lung lesions. At times of early and late treatments, M. haemolytica loads ranged within 3.5-4 and 5.5-6 log10 DNA copies/mL, respectively. Early 2 mg/kg marbofloxacin treatment led to rapid and total elimination of bacteria in all calves. The late treatments induced a reduction of bacterial loads, but 3 of 6 L2 and 1 of 6 L10 calves were still positive for M. haemolytica at day 4. Except for CON calves, all animals exhibited clinical improvement within 24h after treatment. However, early 2 mg/kg treatment was more efficacious to prevent pulmonary lesions, as indicated by the reduction of the extension and severity of gross lesions and by the histopathological scores. These results demonstrated for the first time that a reduced antibiotic regimen given at an early stage of the disease and targeting a low bacterial load could be efficacious in a natural bovine model of pneumonia.